Au carrefour de la médecine et de la littérature : Thomas Sonnet de Courval et Louis de Caseneuve - Koźluk, Magdalena; Pietrzak, Witold (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2014)
This study considers and compares two humanist physicians who lived and were actif in the first half of the 17th century. Both of them interested in literature and medicine created works that testify to the multifaceted culture of the period. Within two different literary genres, satire and emblem, and in their own distinctive way, they deal with the doctrine of the four temperaments. Thomas Sonnet de Courval (1577-1627) perceives the theory from the perspective of the contemporary literary “Debate on Women” which discussed the institution of marriage, and gives not an axiological, but a scientific explanation of the issues raised. On the other hand, Louis de Caseneuve (1577-1627) tries to stress dominant features of the four temperaments in order to facilitate memorizing the physiological doctrine through allegory and mnemotechnics. The works of these two authors are interesting examples of how medicine and literature are interwoven in the humanist culture of the late Renaissance period.